Energy analysis and feasibility of using solar energy in the novel hybrid system of a solar hot plate dryer in Iran - Kimia Taki; Bahram Hosseinzadeh Samani; Mahsa Forouzandeh; Zahra Shafiee (Scientific Reports)
Abstract The drying process in agriculture is energy-intensive and traditionally relies on fossil fuels, which are becoming less reliable and more expensive. This study designed and simulated a hybrid solar hot plate dryer system using the computer to reduce reliance on fossil fuels. The system’s main components are a flat plate collector, photovoltaic panels, and a wind turbine. This system was simulated in three cities of Iran, including Bushehr, Kerman, and Shahrekord, from May 22 to October 23. Results showed that Bushehr had the best wind turbine performance, producing 1.35 × 109 W annually. Shahrekord was ideal for solar energy, reaching solar radiation levels of about 4540 kJ/m2hr in September and generating 6660 W of solar-heated water. Finally, by comparing the yearly yield, it was concluded that Bushehr had a higher yield than the other two cities due to its geographical location, which was 0.301. The results of this research indicated that Iran, with its sunny days and wind energy potential, will be a very suitable place for installing and operating the hot plate solar dryer system. Future studies should look at longer-term simulations, use real-time data, and consider cost-benefit analyses to improve system efficiency and applicability.